2019
DOI: 10.1080/2162402x.2019.1652532
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible electroporation of locally advanced pancreatic cancer transiently alleviates immune suppression and creates a window for antitumor T cell activation

Abstract: Purpose: Local tumor ablation through irreversible electroporation (IRE) may offer a novel therapeutic option for locally advanced pancreatic cancer (LAPC). It may also serve as a means of in vivo vaccination. To obtain evidence of the induction of systemic antitumor immunity following local IRE-mediated ablation, we performed an explorative immune monitoring study. Methods: In ten patients enrolled in a clinical trial exploring the safety, feasibility, and efficacy of percutaneous image-guided IRE in LAPC, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
88
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 39 publications
0
88
0
1
Order By: Relevance
“…Moreover, Zhao et al reported that IRE can potentiate the antitumor efficacy of immunotherapy 5 Scheffer et al demonstrated that IRE of LAPC transiently alleviates immune suppression and creates a window for antitumor T-cell activation. 4,19 In recent years, immune cell therapy has been applied more and more to tumor therapy. 20,21 In TME, T cells are a key component, and treatment with ICIs or adoptive cell infusion has led to breakthroughs in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Zhao et al reported that IRE can potentiate the antitumor efficacy of immunotherapy 5 Scheffer et al demonstrated that IRE of LAPC transiently alleviates immune suppression and creates a window for antitumor T-cell activation. 4,19 In recent years, immune cell therapy has been applied more and more to tumor therapy. 20,21 In TME, T cells are a key component, and treatment with ICIs or adoptive cell infusion has led to breakthroughs in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In IRE 18 , 30 , 31 , 32 , 33 , 34 and ECT with either bleomycin or cisplatin 26 , 35 , 36 , 37 used for cancer treatment, involvement and importance of host immune response was demonstrated, counteracting tumor escape mechanisms. 29 , 38 , 39 After these therapies, dying tumor cells can release specific molecules, which are being recognized by the cells of immune system.…”
Section: Introductionmentioning
confidence: 99%
“…52,58,59 One potential advancement in combination therapy integrates immunotherapy with IRE (and chemotherapy), referred to as "electroimmunotherapy". 9 This is based on the latest findings that IRE induces a systemic immune response 4,60,61 following apoptosis and necrosis of tumor cells, resulting in the release of antigens and damage-associated molecular pattern molecules (DAMPs). These DAMPs induce maturation of dendritic cells (DCs) and other antigen presenting cells (APCs) that can subsequently take up the released antigen epitopes, thereby causing systemic activation of the immune system.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…When robust enough, this systemic T cell response could then lead to regression in distant metastases, a process known as the "abscopal effect". 4,62 However, pancreatic cancers are known for their severely immunosuppressive micro-environment, making it difficult for the activated proinflammatory T-cells to participate in tumor destruction. In order to leverage the patients' own activated immune system through the IRE procedure, a combination with immunotherapy in the form of checkpoint inhibitors or other active immune enhancing drugs may be able to create a synergistic effect.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation